Early postoperative levothyroxine initiation after total thyroidectomy for Graves’ disease - Nagayama, Yuji; Tachibana, Seigo; Fukuda, Takashi; Katsuyama, Kento; Tatsushima, Daisuke; Mori, Yusuke; Shindo, Hisakazu; Takahashi, Hiroshi; Okamura, Misa; Yamaoka, Atsushi; Sato, Shinya; Yamashita, Hiroyuki (Endocrine Journal, 2025)
No evidence-based standards exist regarding levothyroxine (LT4) replacement therapy initiation timing in patients with hyperthyroid Graves’ disease undergoing total thyroidectomy. Although LT4 replacement from the first postoperative day has been the standard of care at our hospital, its clinical validity has not been thoroughly examined. This study investigated the perioperative kinetics of thyroid hormones to assess the safety and efficacy of early LT4 initiation. Thirty patients with Graves’ disease (18 hyperthyroid and 12 euthyroid) and 12 with thyroid nodules who underwent total thyroidectomy were included. Blood samples were collected from each patient for thyroid hormone measurement on the day before surgery (D-1), 15 min after surgery (D0), at 8:00 am on days 1 (D1) and 3 (D3), and 3 weeks (W3) and 3 months (M3) after surgery. In 18 patients with hyperthyroid Graves’ disease, serum free triiodothyronine (FT3) levels significantly decreased immediately after surgery and were within the normal range by D1. Although LT4 was started on D1, FT3 levels continued to decline by D3 and remained low at W3 and M3. Serum FT4 levels followed a slower decline but remained within the normal range for M3. In patients with euthyroid Graves’ disease and those with thyroid nodules, hormone levels stayed within or around the reference range throughout the observation period. In conclusion, initiating LT4 on the day after surgery is safe and effective for maintaining thyroid function in patients with hyperthyroid Graves’ disease undergoing total thyroidectomy. These results could inform future guidelines, supporting earlier postoperative LT4 initiation.